Déconstruire le patriarcat dans l’Église d’Angleterre : enjeux et résistances - Églantine Jamet-Moreau (Revue Française de Civilisation Britannique)
This paper aims to analyse how the issue of women’s access to priesthood and episcopacy in the Church of England has challenged patriarchy. Indeed, the point is not simply to ordain women alongside men, but to reconsider several issues such as the interpretation of Scripture, the teachings of the Church, institutional practices or even ministry itself, in the light of gender equality.